Mental toughness and behavioural perseverance: A conceptual replication and extension - Giles, B.; Goods, P.; Warner, D.; Quain, D.; Peeling, P.; Ducker, Kagan; Dawson, B.; Gucciardi, Daniel (Elsevier Australia, 2018)
© 2017 Sports Medicine Australia. Objectives: The purpose of this study was to conduct a conceptual replication of the proposition that mental toughness is associated positively with behavioural perseverance. Design: Repeated-measures design. Methods: In total, 38 male Australian rules footballers took part in this study (age, 21±3 y; mass, 82.7±11.0kg; height, 1.84±.07m; football experience, 13±4 y). Participants self-reported mental toughness approximately one week prior to their first testing session where we assessed their aerobic capacity via the measurement of peak oxygen consumption (V O 2peak ). Approximately one week later, participants completed a 20m shuttle run test (MST). The final testing session took place approximately one week later, where participants completed a simulated team game circuit (STGC; 60min) to simulate game-relevant level of fatigue, which was followed immediately by a 20m MST. Results: Mental toughness was a salient determinant of the variation in behavioural perseverance under typical circumstances, when prior knowledge from past research was incorporated directly into the estimation process. However, the positive association between mental toughness and behavioural perseverance did not generalise to a performance context in which participants were fatigued. Conclusions: The results of the current study suggest that mental toughness represents a salient psychological correlate of behavioural perseverance in a discrete physical task that taxes the aerobic energy system in some but not all situations. When fatigued, the effect of mental toughness is outweighed by greater underlying fitness.